Hubungan Timbal Balik antara Kinerja Sosial Perusahaan dan Kinerja Keuangan Perusahaan yang Diukur Menggunakan Earning Per Share - Jessica Kartika Halim; Juniarti Juniarti Juniarti (Business Accounting Review, 2016)
This study aimed to prove the reciprocal relationship between corporate social performance and corporate financial performance. This research was carried out on go public companies listed in Indonesia Stock Exchange which published sustainability report and listed in GRI’s database with a sample of 80 observations for model 1 and 98 observations for model 2. Corporate social performance measured by using Sustainability Reporting Index that was assessed by the Global Reporting Initiative (GRI) Index 3.1, whereas the corporate financial performance was measured by using Earning Per Share. The control variables used in this study were leverage and firm size. The results of this study showed that there was no reciprocal relationship between corporate social performance and corporate financial performance. The existency of Undang-Undang No. 40, 2007 indicates that CSR is no longer voluntary, but is an obligation of the company. Therefore, the company's motivation in disclosing CSR solely because of regulations imposed by the government. The results also showed that leverage had negative affect on corporate social performance and corporate financial performance, while firm size had positive affect on corporate financial performance and had not affect on corporate social performance.